2002
DOI: 10.1016/s1010-7940(02)00197-5
|View full text |Cite
|
Sign up to set email alerts
|

Repair of ventricular septal defect and left ventricular aneurysm following blunt chest trauma

Abstract: In children, even minor trauma to the chest can result in cardiac injury. We describe a case of a 13-year-old boy who received blunt chest trauma during a motorcycle accident. He was initially symptom-free but later complained of persistent chest pain and a murmur was noted. An anterior muscular ventricular septal defect was detected one day after the accident, and a left ventricular pseudo-aneurysm developed days later. Both were successfully repaired 3 weeks after the injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
1
9
0
3
Order By: Relevance
“…This may occur as a result of direct cardiac impact or when the heart is compressed between the sternum and the spine. [3578111520] It has also been suggested that a healed congenital VSD with a weakened ventricular septum may re-open with significant blunt trauma to the chest. [6] Delayed inflammatory rupture is thought to occur when cardiac injury causes localised edema with disruption of microvascular flow, leading to infarction, septal liquefaction, and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur as a result of direct cardiac impact or when the heart is compressed between the sternum and the spine. [3578111520] It has also been suggested that a healed congenital VSD with a weakened ventricular septum may re-open with significant blunt trauma to the chest. [6] Delayed inflammatory rupture is thought to occur when cardiac injury causes localised edema with disruption of microvascular flow, leading to infarction, septal liquefaction, and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Whereas, when a large unrestrictive intraventricular communication exists, homodynamic decompensation develops more rapidly. In our case, the VSD was very large and caused a significant left to right shunt.…”
Section: Commentmentioning
confidence: 99%
“…[2,3,13,14] Ül-kemizden de, künt göğüs travma sonrası VSD gelişti-ğini bildirilen çalışmalar [13,15] mevcut olup Kaplan ve arkadaşları [15] koroner arter lezyonu gelişen üç olguya LAD-LİMA baypası yapmışlardır. Bizim hastamı-zın da anjiyokardiyografik inceleme sonrasında cerrahi girişimi planlanmış, ancak ailenin isteği üzerine bir üst merkeze gönderilmiştir.…”
Section: Olgu Sunumuunclassified
“…[2] Çocuk ve ergenlerin göğüs kafesi yapılarının esnek olması nedeniyle dışarıdan bakıldığında görünür bir travma belirtisi olmadan kalp travması görülebilmektedir. [1,3] Postmortem yapılan bir çalışmada ise %15 oranında kalp travmasına rastlanmıştır. [4] Çocuklarda kalp travmaları genellikle olgu sunumları şeklinde bildirilmiştir.…”
unclassified
See 1 more Smart Citation